DISIPLIN, PENGAWASAN DAN PRODUKTIVITAS KERJA - Azimi Faisal; Seno Andri; Zaili Rusli (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Discipline, Supervision and Work Productivity. This study aims to determine how the influence of the partial and simultaneous variables of work discipline and supervision of employee productivity at the Department of Agriculture of Bengkalis Regency. This research uses quantitative method. The population of the research is all employees of the Agriculture Service which amounts to 81 people and all of them are sampled. Data collection techniques are questionnaires and documentation. Data analysis using multiple linear regression. The results showed that there is a significant influence between employee work discipline and supervision on the productivity of employees of the Bengkalis District Agricultural Service. Simultaneously work discipline and work supervision affect the productivity of employment of employees at the Department of Agriculture of Bengkalis Regency, with a very significant level of influence. Where from the determination test R2 known that the variable of work discipline and work supervision has an influence of 70.8% and the rest of 29.2% influenced by variables not examined in this study such as leadership variables, work motivation, incentives and organizational climate.